Role of hemoglobin from blood clam Scapharca kagoshimensis beyond oxygen transport. Issue 1 (May 2015) - Xu, Bin; Zhao, Jun; Jing, Zhao; Zhang, Yanan; Shi, Ying; Fan, Tingjun
Abstract The evolutionary race between hosts and pathogens has led to a variety of adaptations. Little is known about the immunological role of hemoglobin (Hb) in antimicrobial immune responses. Results showed that a 31.2 kDa monodimer Hb (skHbI) and a 57.8 kDa heterotetramer Hb (skHbII) from the blood clam, Scapharca kagoshimensis, had phenoloxidase (PO)-like activities and antimicrobial activities. Both were found capable of oxidizing l-DOPA, catechol and hydroquinone. Their PO-like activities were visibly greatly inhibited by oxidase inhibitors, EDTA, and divalent metal ions, and greatly enhanced by isopropanol and Fe2+, indicating that they have the properties of a metalloenzyme and a catecholase-type PO as well. They also showed obvious anti-bacterial activities against gram-positive bacteria but not against either gram-negative bacteria nor fungi. The anti-bacterial activities levels were a result of the generation of reactive oxygen species (ROS) of superoxide anions. These results indicate that skHbI and skHbII, not only function as iron-containing oxygen carriers, but also exert anti-bacterial activities and catecholase-type oxidizing activities. The fact that skHbII exerts high level of PO-like activity indicates different roles in the innate immunodefense system. These results may improve understanding of the multiple functions of invertebrate Hbs beyond serving as oxygen carriers and may provide insight into how the fundamental and universal mode of the innate immune system has persisted in respiratory proteins throughout the course of evolution.